Let me tell you what I've learned : Texas wisewomen speak - Pierce, Paula Jo (Louann Atkins Temple women & culture series, 2002)
In this collection of interviews conducted by P.J. Pierce, 25 Texas women ranging in age from 53 to 93 share the wisdom they've acquired through living unconventional lives. Responding to the question "What have you found that really matters about life?" they offer keen insights into motherhood, career challenges, being a minority, marriage and widowhood, anger, assertiveness, managing change, persevering, power, speaking out, fashioning success from failure, writing your own job description, loving a younger man, and recognizing opportunities disguised as disaster - to name only a few of their topics